Violence Against Women in Hong Kong: Results of the International Violence Against Women Survey. (November 2015) - Bouhours, Brigitte; Broadhurst, Roderic
In Hong Kong, nearly 1, 300 women participated by telephone in the International Violence Against Women Survey in 2006. One in five respondents had experienced violence since age 16. Sexual violence (13.4%) was more frequent than physical violence (11.7%). Women were more likely to be abused by men they knew (13.5%) than by strangers (8%). Compared with other surveyed countries, Hong Kong recorded among the lowest rates of violence by both intimate partners and non-partners. These results suggest that cultural influences linked to the interaction of modernization and some protective factors found in the adherence to traditional Chinese values are relevant.